Myeloid-derived suppressor cells in secondary sepsis: Is there an association with lethal outcome? - Udovičić, Ivo; Šurbatović, Maja; Rondović, Goran; Stanojević, Ivan; Zeba, Snježana; Djordjević, Dragan; Popadić, Ana; Milosavljević, Snežana; Stanković, Nikola; Abazović, Džihan; Vojvodić, Danilo (Vojnosanitetski pregled, 2021)
Background/Aim. Role of myeloid-derived suppressor cells (MDSCs) in human host response to sepsis still needs to be clarified. The aim of our study was to determine whether frequency and/or absolute numbers of the MDSCs were associated with outcome in critically ill patients with secondary sepsis and/or septic shock. Methods. Total of 40 critically ill patients with secondary sepsis were enrolled in a prospective study. We detected and enumerated both main subsets of MDSCs: granulocytic (G)-MDSCs and monocytic (M)-MDSCs on the Day 1 (the day of hospital admission) and the Day 5 after the. The primary end-point was hospital mortality. Results. Increased frequencies and absolute numbers of subpopulations corresponding to MDSCs were associated with poor outcome. As far as relative kinetics was concerned, in both survivors and non-survivors, sepsis duration from 1th to 5th day was accompanied by an increase in MDSCs values of both investigated subpopulations. In contrast to findings of stepwise multivariate logistic regression analysis of the variables on the Day 1, on the Day 5 it was determined that the Sequential Organ Failure Assessment (SOFA) score (OR 2.350; p < 0.05) and G-MDSCs frequencies (OR 3.575; p < 0.05) were independent predictors of lethal outcome. Conclusion. These findings suggest harmful role of MDSCs in secondary sepsis.